Hindi News Paper and Changing Trends of Hindi Language - DR. GUNJAN SHARMA; MR MADHUR SHARMA (Journal of Advanced Research in Journalism & Mass Communication, 2024)
In this era of information technology, every person has started playing the role of news. As globalization has made the world small by making small news viral through social media, through social media we can make awareness of every event to any corner of the world. In such a situation it is very difficult to predict the future of the media. By the change of the time we can even see that the printed newspaper is read in digital platform like Telegram. Now, newspapers have come in the form of paper as well as e-paper on the computer, laptop or mobile phone. It is also not necessary that the nature of future libraries should be the same as e-library or digital library. In this advanced era of information technology, the world has become a global village and you can read the newspaper from any corner of the world whenever and wherever you want, provided you know the language of that newspaper. Now the form of electronic media is also changing. Even without TV (Television), we are watching any TV channel on the computer, laptop or mobile. Reliability is considered the life of journalism and on this belief, people accept the things printed in newspapers as true but today’s modern journalism has become professional and that professionalism has taken out the “life” of that natural and natural “credibility”. By creating the credibility of its convenience, it has breathed life into the modern journalism of the new age. It is not that earlier, keeping newspapers alive did not require the protection of those in power or resources. But then the intentions of the patrons were not so bad and they were able to bear the criticism of themselves or their class. Today, being our newspaper or our media means “truth” to us as well. What we speak, what we write and what we show is natural, because we have bought the ownership of a machine that spews the “truth” by investing huge sums of money. Seeing the eyes of the elders, everyone is selling it at the crossroads by claiming ownership of “Truth” even on a small scale. Governments are also liking these wholesale and retail sellers of “Truth” and according to the status of these vendors, their selling “Truth” is being bought. This is the truth for those who invest in “truth” business. Newspaper and press were two sides of the same coin. It could never have been imagined to print a newspaper without a press.